Peran Teknologi dalam Manajemen SDM : Sebuah Studi Literature - Putri Cinta Maulida Fahsa; Putri Adelia Anjani; Alya Shalsabilla Juliyanti; Netty Merdiaty (STIKes Ibnu Sina Ajibarang, 2025)
The Human Resources Information System (HRIS) enables more efficient management of employee data and supports the implementation of HR policies that are more transparent and accurate. The development of information technology has had a significant impact in various fields, including Human Resources (HR) management. In addition, technology also facilitates better communication between management and employees, allows independent benefit updates, and makes it easier to implement digital-based training.